STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PAI MELALUI MEDIA TIKTOK SISWA SMP 4 KOTA PROBOLINGGO - Salsabila, Rahil; Muhammad, Devy Habibi (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
This article is an opinion based on the author's previous research on the development of learning media. PAI teachers can increase learning motivation through tiktok media by creating creative educational content, utilizing popular trends, and encouraging student participation through related challenges or projects. Short video formats can be used for concise and interesting delivery, with the addition of music and various features to capture students' attention. Collaborative strategies, the use of custom hashtags, and adapting the curriculum to tiktok trends can help build a dynamic and relevant learning community. The tiktok application comes with subtitles from the community, and ironically Gen Z really likes this application. The tiktok application can be a fun and interesting learning medium. The use of the tiktok application as an interactive learning medium aims to enable students to understand and evaluate the learning process carried out by the teacher. Learning media allows teachers to express what cannot be taught, so that the learning process becomes more effective and efficient. The tiktok application allows teachers to easily create interactive learning that can adapt to the situation, environment and students' conditions. Keywords:  PAI Teacher Strategy; Learning Motivation; TikTok Application Media.